Clinical use of whole genome sequencing for Mycobacterium tuberculosis. Issue 1 (December 2016) - Witney, Adam; Cosgrove, Catherine; Arnold, Amber; Hinds, Jason; Stoker, Neil; Butcher, Philip
Abstract Drug-resistant tuberculosis (TB) remains a major challenge to global health and to healthcare in the UK. In 2014, a total of 6, 520 cases of TB were recorded in England, of which 1.4 % were multidrug-resistant TB (MDR-TB). Extensively drug-resistant TB (XDR-TB) occurs at a much lower rate, but the impact on the patient and hospital is severe. Current diagnostic methods such as drug susceptibility testing and targeted molecular tests are slow to return or examine only a limited number of target regions, respectively. Faster, more comprehensive diagnostics will enable earlier use of the most appropriate drug regimen, thus improving patient outcomes and reducing overall healthcare costs. Whole genome sequencing (WGS) has been shown to provide a rapid and comprehensive view of the genotype of the organism, and thus enable reliable prediction of the drug susceptibility phenotype within a clinically relevant timeframe. In addition, it provides the highest resolution when investigating transmission events in possible outbreak scenarios. However, robust software and database tools need to be developed for the full potential to be realized in this specialized area of medicine.